Compositional characteristics of mineralised and unmineralised gneisses and schist around the Abansuoso area, southwestern Ghana - Kazapoe, R.W.; Okunlola, O.; Arhin, E.; Olisa, O.; Kwayisi, D.; Dzikunoo, E.A.; Amuah, E.E.Y. (Applied Earth Science, 2023)
Gold-bearing granitoid deposits have recently been discovered in the Birimian of Ghana but their mode of formation and ore genesis remain enigmatic. This study presents petrographic, and geochemical characteristics of mineralised and unmineralised (gold grade >0.05 and <0.05 g/t respectively) granitoids (now gneisses) and schists (metasedimentary) to evaluate their petrogenesis/provenance, and relationship to gold mineralisation in the Abansuoso area. The unmineralised rocks comprise biotite- and hornblende-biotite gneisses, sericite-quartz, carbonate-sericite, and biotite-quartz schist. The mineralised varieties are biotite-, muscovite gneiss, iron-carbonate-sericite, carbonate-sericite-quartz, chlorite carbonate, and biotite-carbonate schist. The mineralised and unmineralised gneisses are both metaluminous and peraluminous. Both mineralised and unmineraised gneiss and schist show Nb-Ta trough, depleted LILE and enriched HFSE although widespread overall trace element concentrations for the mineralised rocks on UCC-normalised multi-element diagram, suggestive of their formation in an arc setting. This suggests coeval granitic plutonism and sedimentation with subduction-accretion during the Eburnean orogeny, hence, mineralisation may be orogenic-type.
Research Article
Keywords: Geochemistry; gold mineralisation